Indian Naval Expansion and its Strategic Partnership with US in the Indian Ocean Region: Implications for Pakistan - Dr. Sadia Rafique; Saira Masood (Journal of Professional Research in Social Sciences, 2022)
India’s quest for extraordinary power status is submitted in changing its naval force into a blue water navy alongside cutting edge stages to secure the vital public interests in Indian Sea. There are wide range of naval operations that are supported by naval diplomatic exercises like Assured Second Strike Capability. These developments in conventional asymmetries among the regional navies indicate that a strategic imbalance is growing in Indian Ocean shifting the balance of power towards India. This paper explores the maritime strategies of India in various dimensions. This study also aims to find how India made alignment or alliances with USA in achieving its desired policies. It is also tried to cover implications for Pakistan in this regard. To achieve these objectives key indicators of realism are used in theoretical framework. An extensive literature available was synthesized as well. At the end a comprehensive analysis is made while suggesting key recommendations later.